KUALITAS ORGANOLEPTIK ES KRIM SUSU KAMBING DENGAN PENAMBAHAN PATI KENTANG (Solanum tuberosum L.) - Citra Prameswari; Dewiarum Sari; Salvian Setyo Prayitno (JANHUS: Jurnal Ilmu Peternakan Journal of Animal Husbandry Science, 2026)
Goat's milk is a livestock food that can be processed into various kinds of preparations, one of which is ice cream. One of the vegetable ingredients that can be used in making ice cream is potatoes which are used as starch. Potato starch can be used as a natural stabilizer in ice cream because it contains high amounts of amylose and amylopectin. This study aims to determine the organoleptic quality (color, aroma, taste, texture and level of preference) of goat's milk ice cream added with potato starch at concentrations P0 (0.3% CMC addition), P1 (1.5% potato starch addition). P2 (addition of 3% potato starch) and P3 (addition of 4.5% potato starch). The design used in this research was a Randomized Block Design (RAK) with a non-factorial pattern for organoleptic testing (color, aroma, taste, texture and level of liking). The results of analysis of variance (ANOVA) showed that differences in the concentration of added potato starch showed a significant effect (P<0.05) on the organoleptic quality (color, aroma, taste, texture and level of preference) of goat's milk ice cream. Based on organoleptic quality, the best treatment was treatment P3 (addition of 4.5% potato starch).